The Expertise Function of Amicus Curiae in International Criminal Justice - E. A. Kopylova (Московский журнал международного права, 2020)
INTRODUCTION. While abroad over the past decades both comprehensive research and publications touching on individual aspects of amicus curiae in international law have been edited, it garnered only very little scholarly attention in Russian scientific literature. The frequency of its use and the nature of its impact on international judicial and quasi-judicial proceedings vary among branches of international law. This article considers one of the functions that an amicus curiae may perform in international criminal proceedings – the function of expertise.MATERIALS AND METHODS. The article is based on the existing volume of scientific knowledge in different branches of international law, such as law of international treaties, international criminal law, law of international organizations, human rights law, international economic law, history of international law and others. The research is based on the conclusions and inferences achieved mainly in the foreign doctrine of international law including publications of this year, due to the low degree of development of the topic in Russian literature. The empirical basis of the research is formed by international legal acts, internal acts of international criminal tribunals, materials of proceedings relating to interstate disputes, international advisory proceedings, practice of international criminal courts. The methodology used is a combination of general scientific methods of cognition (methods of analysis and synthesis, induction and deduction, critical and dialectical) and private scientific methods typical for legal sciences (historical, comparative).RESEARCH RESULTS. International criminal courts actively rely on the amicus curiae mechanism to obtain information, both legal and factual, on issues under consideration in criminal proceedings. The admission of amicus curiae to international criminal proceedings is entirely at the discretion of the judiciary. In practice, amicus curiae applications are submitted by subjects of international law, international non-governmental organizations, natural and legal persons and professional associations.DISCUSSION AND CONCLUSIONS. Too frequent use of amicus curiae mechanism seems to be difficult to reconcile with the iura novit curia maxima. Its current practice provides fertile ground for all kinds of abuse and needs to be reviewed. In particular, the experience of the UN International Court of Justice, the International Tribunal for the Law of the Sea and the UN Commission on International Trade Law could be instructive in this regard.